From parametric decoding of simple mental states to neurofeedback: insights into the neuroscience of cognitive control - Sousa, Teresa Maria da Silva (2017)
Tese de doutoramento em Engenharia Biomédica, apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra